CORONAVIRUS ANXIETY IN NURSES WORKING IN AN INTENSIVE CARE UNIT IN LIMA, 2021 - Balladares Chavez, Maria del Pilar (2022)
Objective: The study aimed to determine anxiety due to coronavirus in nurses who work in an Intensive Care Unit in Lima, 2021. Materials and methods: This research had a quantitative approach and its methodological design was descriptive and cross-sectional. The population was composed of 36 nurses who work in an intensive care unit. The technique used was the survey and the instrument applied was the coronavirus anxiety scale (CAS). Results: Regarding the age of the participants, the minimum was 25 years, the maximum was 53 years and the average was 38.57 years. Regarding gender, 66.7% (n=24) were women and 33.3% (n=12) were men. Regarding anxiety due to coronavirus in nurses, those with dysfunctional anxiety predominated with 61.1% (n=22) and followed by those without dysfunctional anxiety with 38.9% (n=14). According to their items, in dizziness, those who have for more than 7 days prevailed with 44.4% (n=16), in sleep disorder those who have several days prevailed with 44.4% (n=16), in loss of appetite those who have several days prevailed with 47.2% (n=17) and finally in abdominal discomfort those who have several days prevailed with 44.4% (n=16). Conclusions: Regarding coronavirus anxiety in the nursing staff, those with dysfunctional anxiety and those without dysfunctional anxiety predominated